The Impact of Physical and Human Capital on The Economic Growth of Agricultural Sector in South Sumatera - Kadir, Syamsurijal Abdul; Azwardi, Azwardi; Wardhani, Rulyanti Susi; Novalia, Nurkardina; Maulana, Ahmad (International Journal of Economics and Financial Issues, 2018)
South Sumatra Province is one of the provinces with major potential in the agricultural sector which is accounted for 16.60 percent in the GDP formation, it is necessary efforts so that the production of the agricultural sector can be maintained and improved. The purpose of this study is to analyze the effect of the agricultural sector capital expenditure (physical capital) and education, health, and labor (human capital) to economic growth in South Sumatra. The data used in this study are the panel data which are time series and cross section in 14 districts/cities in South Sumatra. The research using linear regression analysis method with Fixed Effect Model. The analysis showed education, health, labor and agriculture sector capital spending has significant positive effect on economic growth as measured by the agricultural sector GDP. Keywords: capital expenditure, education, health, employment, economic growth JEL Classifications: I25, I15